The Roles of Agility, Supply Chain Sustainability, and Risk Management on Operations Performance in Manufacturing Industry - Ahmad Syamil; Nazaruddin La Ode; Bernadetha Christy Rosariana; Livia Maharani Aristy; Rut Liesl (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates the role of sustainable supply chain practices and risk management in enhancing manufacturing agility and operational performance, with a particular focus on the underexplored context of developing countries such as Indonesia. Data were collected from 255 managers and executives across the manufacturing, operations, logistics, and supply chain sectors using a structured questionnaire based on a five-point Likert scale. The responses were analyzed using SmartPLS. The results indicate that environmental practices positively influence both manufacturing agility and operational performance, although the effect on operational performance is relatively weaker yet remains statistically significant. Risk management emerges as a critical enabler, contributing positively to both agility and performance outcomes. Among the variables examined, manufacturing agility exerts the strongest influence on operational performance, underscoring its pivotal role in achieving competitive advantage. By integrating supply chain sustainability, risk management, manufacturing agility, and operational performance into a unified framework, this study addresses key research gaps and provides valuable theoretical and practical insights.